2021
DOI: 10.46827/ejsss.v6i4.1083
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Peer Influence and Sexual Behaviour of in-School Adolescents in South East, Nigeria

Abstract: This study examined the relationship between peer influence and sexual behaviour of in-school adolescents in South East Zone of Nigeria. The population of this study comprised 137, 095 in-school adolescents in senior secondary II in public secondary schools. The sample of the study was 1200 senior secondary II in-school adolescents. Three research questions and one hypothesis were formulated for the study and the study adopted correlation survey design. Two instruments, namely: Peer Influence Questionnaire (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…It also agreed with [10] study which showed that peer influence positively predicted risk taking behaviour in adolescents. The study was also in consonance with [11] research which reported that what was seen as peer influence for the in-school adolescents was making friends on facebook and doing homework with friends of opposite sex, among others. The study finding supported the assumptions of the social contagion theory.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It also agreed with [10] study which showed that peer influence positively predicted risk taking behaviour in adolescents. The study was also in consonance with [11] research which reported that what was seen as peer influence for the in-school adolescents was making friends on facebook and doing homework with friends of opposite sex, among others. The study finding supported the assumptions of the social contagion theory.…”
Section: Discussionsupporting
confidence: 84%
“…A study showed that peer influence positively predicted risk taking behaviour in adolescents [10]. In another study by [11] reported that what is seen as peer influence for the in-school adolescents was making friends on facebook and doing homework with friends of opposite sex, and that the in -school sexual behaviour are attraction to the opposite sex and enjoying sexual intercourse under the influence of alcohol hence the need for urgent sexual education and counseling. A study conducted by [12] observed that boys were significantly more susceptible to peer influence than girls, and that not all adolescents are susceptible to peer influence.…”
Section: Introductionmentioning
confidence: 99%
“…By sequencing the genomes of bacteria isolated from human cases and animal reservoirs, researchers can trace the source of infection and identify factors contributing to disease transmission. This information can help inform control measures, such as improved food safety practices or targeted vaccination campaigns, to prevent future outbreaks (Akunne & Etele, 2021, Chigbu, et. al., 2021.…”
Section: Technological Advancements In Surveillancementioning
confidence: 99%
“…One Health is a collaborative, interdisciplinary approach that recognizes the interconnectedness of human, animal, and environmental health. Effective One Health surveillance is essential for early detection, rapid response, and control of zoonotic diseases and other health threats that transcend species boundaries (Akunne & Etele, 2021, Chigbu, et. al., 2021, Zinsstag, et.…”
Section: Strategies For Enhancing One Health Surveillancementioning
confidence: 99%
“…Additionally, AI can facilitate adaptive policy design and implementation by analyzing vast amounts of data and identifying trends, patterns, and insights that inform policy decisions and interventions. By leveraging AI-generated insights, policymakers can design more effective and targeted interventions to promote financial inclusion and poverty alleviation, ensuring that resources are allocated efficiently and equitably to address the most pressing needs and challenges (Chigbu, et al, 2021). In conclusion, AI presents a wealth of opportunities to advance financial inclusion and poverty alleviation through advanced data analytics, AI-driven financial services, and targeted interventions.…”
Section: Opportunities Offered By Ai In Financial Inclusion and Pover...mentioning
confidence: 99%